2015
DOI: 10.3390/bios5030417
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Nanoholes for Optical Biosensing

Abstract: Sub-wavelength diameter holes in thin metal layers can exhibit remarkable optical features that make them highly suitable for (bio)sensing applications. Either as efficient light scattering centers for surface plasmon excitation or metal-clad optical waveguides, they are able to form strongly localized optical fields that can effectively interact with biomolecules and/or nanoparticles on the nanoscale. As the metal of choice, aluminum exhibits good optical and electrical properties, is easy to manufacture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A survey on modifications of optical fibers and applications in various fieldsespecially diagnosticsin combination with a discussion of future challenges are given in [135]. Nanowires, nanoparticles, and nanoholes are used for biosensing [136]. A large number of types of fiber sensors are reviewed [137] and challenges and prospects are discussed recently [138].…”
Section: Fibers and Waveguides Without Structurementioning
confidence: 99%
“…A survey on modifications of optical fibers and applications in various fieldsespecially diagnosticsin combination with a discussion of future challenges are given in [135]. Nanowires, nanoparticles, and nanoholes are used for biosensing [136]. A large number of types of fiber sensors are reviewed [137] and challenges and prospects are discussed recently [138].…”
Section: Fibers and Waveguides Without Structurementioning
confidence: 99%
“…Barrios et al [46] demonstrated the applicability of aluminum nanohole arrays (NHAs), deposited onto a microscope coverslip, for sensing applications. The pre-polymerization mixture was deposited onto the NHAs, and the light was efficiently confined inside favoring the photopolymerization of submicron-sized MIP patterns selective to rhodamine 123 (R123), as a model template molecule.…”
Section: Fiber Optic and Evanescent Wave Biosensorsmentioning
confidence: 99%
“…Evaluation of the selective recognition of R123 by the imprinted polymer was carried out by fluorescence lifetime imaging microscopy with single photon timing measurements. A similar approach has been applied to the development of biosensors for the detection of biotin as a model analyte, in combination with glass, polycarbonate compact discs (PC CDs) or transferable aluminum NHAs onto flexible pressure-sensitive adhesive tapes using label-free SPR measurements [46,47].…”
Section: Fiber Optic and Evanescent Wave Biosensorsmentioning
confidence: 99%
“…Further, aluminium can be easily manufactured and it also displays great optical and electrical characteristics. In the biosensor, aluminium utilization seems to be not preferable because of the corrosion due to oxidation and pitting problems 28 . Other than oxidation matter, aluminium is apparently unstable in acidic and alkaline conditions, which can be validated using the outcome of sensor's performance at different pH.…”
mentioning
confidence: 99%